2001
DOI: 10.1128/jcm.39.5.1696-1701.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hexaplex Assay for Detection of Respiratory Viruses in Children

Abstract: The Hexaplex assay (Prodesse, Inc., Milwaukee, Wis.) is a multiplex reverse transcriptase (RT)-PCR assay for the detection of parainfluenza virus types 1, 2, and 3, respiratory syncytial virus (RSV) types A and B, and influenza virus types A and B. We evaluated the Hexaplex assay in comparison with conventional viral cell cultures and rapid enzyme immunoassays (EIAs) for RSV (Directigen; Becton Dickinson Inc., Cockeysville, Md.) and influenza A virus (Abbott Test Pack; Abbott Laboratories, Abbott Park, Ill.) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
130
1
12

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 38 publications
8
130
1
12
Order By: Relevance
“…Three coinfections were identified. This represented 0.92% of the total and is fewer than the numbers reported in many studies that have used RT-PCR (9,12). However, the coamplification of all target amplicons from plasmids containing cloned amplicons (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Three coinfections were identified. This represented 0.92% of the total and is fewer than the numbers reported in many studies that have used RT-PCR (9,12). However, the coamplification of all target amplicons from plasmids containing cloned amplicons (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…This figure may, in fact, represent an underestimate, given the lower sensitivity of RSV cultures compared with polymerase chain reaction (PCR). 21 Most important, the rate of respiratory complications among patients whose nasal cultures yielded RSV did not significantly differ from that of patients who were RSV-negative, although a post hoc analysis did reveal a higher rate of tracheobronchitis and hypoxemia among the former patients. Univariate and multivariate analyses failed to identify positive RSV culture as a risk factor for respiratory complications.…”
Section: Discussionmentioning
confidence: 96%
“…DFA detection is more rapid but less sensitive than viral culture, and results may be affected by specimen quality (ie, presence of intact, infected cells), virus type, and interpretation of a positive result, which is subjective and requires a great deal of technical skill. 2,[7][8][9][10] DFA is also unable to detect minor variations in amino acid sequence on envelope or capsid proteins. 11 Viral culture is still considered the "gold standard" for respiratory virus detection, but is limited by a prolonged result turnaround time (ie, 2 days to 1 week) and is dependent on stringent specimen transport and storage conditions to preserve the infectivity of the virus.…”
mentioning
confidence: 99%
“…11 Viral culture is still considered the "gold standard" for respiratory virus detection, but is limited by a prolonged result turnaround time (ie, 2 days to 1 week) and is dependent on stringent specimen transport and storage conditions to preserve the infectivity of the virus. 9,[12][13][14][15] Although the combination of both these techniques can provide an increase in the number of positive results, a significant proportion of specimens still remain negative, despite clinical suspicion of viral infection. 8 Several studies have shown that polymerase chain reaction (PCR) amplification can resolve the intrinsic limitations associated with traditional diagnostic techniques by combining increased sensitivity, specificity, and rapid result turnaround time.…”
mentioning
confidence: 99%